Pulmonary atresia with intact ventricular septum and congenital left ventricular aneurysm. (22nd April 2018) - Ng, Benton; Hickok, Rhiannon; Stapleton, Gary; Karl, Tom
Abstract: Pulmonary atresia with intact ventricular septum and congenital left ventricular aneurysms are both rare, representing <1 and <0.1% of CHD, respectively. The association of left ventricular aneurysms and pulmonary atresia with intact ventricular septum has been documented in the literature, but all the previous case reports have involved children with acquired left ventricular aneurysms. We report an interesting case of a child with both pulmonary atresia with intact ventricular septum and a congenital left ventricular aneurysm. The combination of these two lesions ultimately affected the course of clinical care for the patient.